Mobile-Based Mathematics Quiz Application (Case Study of International Mental Arithmetic Course) - Boynge, Abyan Taqy; Arman, Shevti Arbekti; Gumelar, R. Tommy (Yayasan Adra Karima Hubbi, 2023)
A mobile application is a program that can run on the operating system of a mobile device, such as a smartphone. The background of this research is that when registering and taking courses at IMA Indonesia, the course institutions are still using conventional learning methods and not applying technology to enhance more interactive learning. The purpose of this study was to design a Mathematics Application for learning mobile-based arithmetic quizzes for elementary school students at IMA Indonesia. In this study, researchers used qualitative research methods. The use of qualitative methods can provide a broad understanding of the experiences and views of students and teachers regarding the effectiveness of using Mathematics applications in arithmetic quizzes. Qualitative data collection methods through observation and interview techniques. The application is designed using the Extreme Programming (XP) method. The goal of the XP method is to produce quality, productive, and cost-effective software during changes in the software development stage. The results of this study designed a Mathematics Application for mobile-based arithmetic quizzes using the Flutter framework and the Firebase database which has learning menu contents and quizzes. Based on the conclusions of this study, namely the application of mathematics to Android-based arithmetic quizzes at IMA Indonesia can improve the quality of learning in the application of mathematics to Android-based arithmetic quizzes